Peningkatan Kenyamanan Termal dan Pencahayaan Alam Gedung Sekolah Dasar di Kawasan Padat Hunian di Surabaya - N. Ekasiwi, Sri Nastiti; Ngurah Antaryama, I Gusti; Sudarma, Erwin; Defiana, Ima; Dinapradipta, Asri; Badai Samodra, FX Teddy; Soemardiono, Bambang; Irvansjah, I; Mahendra, Angger Sukma; Erwindi, Collinthia (Arsitektura : Jurnal Ilmiah Arsitektur dan Lingkungan Binaan, 2020)
A humid tropical climate characterized by high temperatures, relative humidity and solar radiation results in uncomfortable environmental conditions. Discomfort will be worse if the building is in a dense urban area. Densely building masses often weaken the local wind speed which is necessary for evaporative cooling process in tropical climate. In addition, the narrow distance between buildings can reduce access to daylight. Both of these environmental problems were experienced by SDIT Al Uswah Surabaya, which building is located in a densely populated neighbourhood. Along with the development program of educational facilities and infrastructure at the school, improving environmental conditions with passive concept is maintained and prioritized. Embodiment of the environment with the Selective Environment approach is used in this activity. The results of this activity will be in the form of design proposals for improving ventilation and lighting in classrooms. The limitation of expanding openings becomes an obstacle in fulfilling the natural ventilation and lighting requirements. In addition, the design of a three-storey building with a single loaded corridor requires special consideration for the design of sun shading that is safe for elementary school-age children, but still supports passive lighting and ventilation.